Ecophysiology of Sarcocornia neei (Amaranthaceae) from two wetlands of the central coast of Lima, Peru - La Rosa Loli, Rafael; Flores Núñez, Astrid Carolina; Chávez Gamarra, Mily Malú; Flores Quintana, Gonzalo; Alcalde Alvites, Miguel; Zeña Carrasco, Héctor Josué; Arieta Guardia, Lisbeth Úrsula; Valderrama Bhraunxs, Noelia del Carmen; Huerta Jara, Cesar Kennedy; Sandoval Peña, Gustavo Adolfo (Instituto de Ecología, A.C., 2020)
Background and Aims: The wetlands of the central coast of Lima, Peru, are being negatively impacted by anthropic activity, because human settlements have been established in the vicinity of these fragile ecosystems. Sarcocornia neei is a halophytic Amaranthaceae, which inhabits these wetlands and with potential to be used as food. However, it is being displaced by this human activities, while basic aspects of its biology remain unknown. Hence, our goal was to investigate the ecophysiology of this species, under greenhouse and laboratory conditions, looking at the possibility of being grown outside its natural environment.Methods: Plants of S. neei were collected in both Ventanilla and Paraíso Wetlands, Lima, Peru. For the germination test, 600 seeds were subjected to different concentrations of NaCl (0 M, 0.1 M, 0.3 M and 0.58 M), with three repetitions for 15 days. Cuttings were also planted in organic substrate and adding the same concentrations of salt, with three repetitions for four months. At the end of this period histological sections were made and protein extracts were also realized.Key results: A better germination was obtained in 0.3 M of NaCl. There were no significant differences in the growth of cuttings. Histological variations were found in the stems depending on the treatments and there were no significant differences in the total protein concentration, although overexpression of low molecular weight proteins was found in the treatment of 0.58 M NaCl.Conclusions: The results show that this species could be cultivated in saline lands and used in human or animal feed, or as a promising species in the decontamination of lead-contaminated saline soils.